Descriptive study of plant resources in context of the ethnomedicinal relevance of indigenous flora; a case study from Rajouri-Poonch region of Himalaya - Wani, Zishan Ahmad; Pant, Shreekar; Singh, Bikarma (Ethnobotany Research and Applications, 2021)
Background: The study is an attempt to document the medicinal plants used in traditional health care systems in Rajouri-Poonch region of Himalaya. The study also highlights some direct relationships of botanical diversity with various social and cultural aspects, along with quantitative indices to validate the data investigated. This study presents the pioneering attempt to analyze the effect of various variables (age, gender, and education) for ethnobotanical data in Jammu and Kashmir. Methods: Convenience sampling has been used by selecting a total of 128 informants. Questions regarding the utilization of different plants, their parts used, diseases treated, and mode of administration were asked through using questionnaires prepared for the purpose. Data waweres analyzed through different quantitative ethnobotanical indices. Results: A total of 92 plant species belonging to 86 genera and 48 families investigated to be used in the traditional health care system of the region. Rosaceae is the most dominant family followed by Lamiaceae, Fabaceae, and Asteraceae. Most of the documented species were herbs (37.5%) followed by shrubs (17.96%), trees (11.71%), and climbers (4.68%). Leaves were the most common part used in herbal preparations followed by roots, whole plants, seeds, fruits, aerial parts, rhizomes, flowers, cloves and bark. The main method of preparation was decoction followed by extract, paste, powder, chewed, cooked, infusion, poultice and roasted. Species with the highest RFC were Taraxacum officinale (0.82), Raphanus sativus (0.68) and Allium sativa (0.67). Informant Consensus Factor for each disease category ranges from 0.94 to 0.97. The results reveals that there is a strong positive correlation between age and citations (r=0.64) and a negative correlation between the level of education and citations (r = -0.34). Conclusion: Traditional knowledge is draining of rapidly because of modernization and urbanization. There is an immediate need to draft policies for documentation and preservation of such knowledge. Further, plants with high Relative Frequency of Citations and Fidelity Level should be prioritized for bioprospection studies like phytochemical investigation, pharmacological studies, microbiological and toxicological enquires to draw general conclusions on ethnopharmacological relationships. Keywords: Rajouri-Poonch, Variables, Quantitative, Traditional, Correlation